Kleine-Levin syndrome: interface between neurology and psychiatry - Justo, Luís Pereira [UNIFESP] (2007)
We report the first episode of Kleine-Levin (KLS) syndrome in a 17-year-old male. The illness onset, clinical features, neuropsychological evaluation and polysomnographic recording are described. Typical symptoms hypersomnia, hyperphagia and sexual disinhibition were observed besides behavioral disturbances, polysonographic and neuropsychological alterations. Behavioral disturbances similar to a manic episode including psychotic symptoms were relevant. The pharmacologic treatment included lithium, methylphenidate and risperidone. The introduction of risperidone aimed the control of psychotic symptoms and the persistent manifestations of hypersexuality after sleepness control and to the best of our knowledge there are no other report regarding risperidone use for KLS in the literature.